Smoking, Alcoholic and Drugs Habit of Street Children of Kathmandu Valley - Kunwar, Mala (Nepal Journal of Multidisciplinary Research, 2022)
Street children are those who always spend their time in the street. Being on the streets has various causes and effects. Smoking, drinking, and drug usage are more common among street children all across the world. The study's objective is to determine whether street children in the Kathmandu Valley smoke, drink, or use drugs. A total of 234 street children from the Kathmandu valley were purposefully chosen. The data was gathered using a mixed method. According to the report, more than 60% of street children smoke, drink, or use drugs on a regular basis. Both male and female street children were found to have a high prevalence of drug use. Because they had no one to look after them, it was exceedingly difficult to keep them from becoming drug addicts. In order for street children to feel comfortable and have a brighter future, the government should seek to reintegrate them with their families.